Computational Fluid Dynamics Analysis of Nasal Airway Changes after Treatment with C-Expander - Wang Xiao; Siling Liu; Yanqin Lu; Lei Lei; Ning Liu; Xiaoping Shen; Yuhong He; Ousheng Liu (Applied Bionics and Biomechanics)
The use of the C-expander is an effective treatment modality for maxillary skeletal deficiencies which can cause ailments and significantly reduce life expectancy in late adolescents and young adults. However, the morphological and dynamic effects on the nasal airway have not been reported. The main goal of this study was to evaluate the nasal airway changes after the implementation of a C-expander. A sample of nine patients (8 females, 1 male, age range from 15 to 29 years) was included. The morphology parameters and nasal airway ventilation parameters of pretreatment and posttreatment were measured. All study data were normally distributed. A paired t-test was used to evaluate the changes before and after treatment. After expansion, the mean and standard deviation values of intercanine maxillary width (CMW) and intermolar maxillary width (MMW) increased from 35.75±2.48 mm and 54.20±3.17 mm to 37.87±2.26 mm (P<0.05) and 56.65±3.10 mm (P<0.05), respectively. The nasal cavity volume increased from 20320.00±3468.25 mm3 to 23134.70±3918.84 mm3 (P<0.05). The nasal pressure drop decreased from 36.34±3.99 Pa to 30.70±3.17 Pa (P<0.05), while the value of the maximum velocity decreased from 6.50±0.31 m/s to 5.85±0.37 m/s (P<0.05). Nasal resistance dropped remarkably from 0.16±0.14 Pa/ml/s to 0.08±0.06 Pa/ml/s (P<0.05). The use of C-expander can effectively broaden the area and volume of the nasal airway, having a positive effect in the reduction of nasal resistance and improvement of nasal airway ventilation. For patients suffering from maxillary width deficiency and respiratory disorders, a C-expander may be an alternative method to treat the disease.